-6+2t=3t-(6+5)

Simple and best practice solution for -6+2t=3t-(6+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6+2t=3t-(6+5) equation:


Simplifying
-6 + 2t = 3t + -1(6 + 5)

Combine like terms: 6 + 5 = 11
-6 + 2t = 3t + -1(11)

Multiply -1 * 11
-6 + 2t = 3t + -11

Reorder the terms:
-6 + 2t = -11 + 3t

Solving
-6 + 2t = -11 + 3t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-3t' to each side of the equation.
-6 + 2t + -3t = -11 + 3t + -3t

Combine like terms: 2t + -3t = -1t
-6 + -1t = -11 + 3t + -3t

Combine like terms: 3t + -3t = 0
-6 + -1t = -11 + 0
-6 + -1t = -11

Add '6' to each side of the equation.
-6 + 6 + -1t = -11 + 6

Combine like terms: -6 + 6 = 0
0 + -1t = -11 + 6
-1t = -11 + 6

Combine like terms: -11 + 6 = -5
-1t = -5

Divide each side by '-1'.
t = 5

Simplifying
t = 5

See similar equations:

| 3x=y/9 | | ((d-4)/4)^2=49 | | -102=-6(8n+1) | | 2(3-6n)=102 | | 3[m+(-5)]=2m+10 | | 30+-10= | | 5-4(8x-2)=0 | | -5x+5(8x-6)=180 | | A=7/4 | | a+2=6a-6 | | 3t^3-30t^2-21t=0 | | 22=5a | | 13=3a+5-2a-7 | | -28=-28+v | | 6x+2x-16=-24 | | 40x+104=40x+80 | | x^2(x-8)=0 | | -7(1-2b)=-105 | | -8-12y=20 | | -7(1-8m)=-175 | | 2/x-1-4/x-3/x | | -200=-8(1+8r) | | -1+4(-6+5n)=-125 | | 5.5x^2-24x+26=0 | | 3x+2y=247 | | 4+5=6n+7 | | .5timesK+8=K-4 | | k-5=55,000 | | 9x-3+2x+20=15+4x+2x+7x | | 4w-x+20=w+21 | | 70+6y=-4y | | 3x^3/4=24 |

Equations solver categories